The Effect of Compensation, and Work/Family Conflict Through Job Satisfaction on Employee Retention - Rizkie Arianti Putri Noor; Justine Tanuwijaya (Publikasi Indonesia, 2024)
This study aims to analyze the effect of compensation and work/family conflict that is allegedly mediated by job satisfaction on employee retention. The data used in this study is data obtained from a questionnaire survey distributed in several type-A hospitals in DKI Jakarta. The smartPLS software is used to analyze the data. The research uses surveys obtained from structured questionnaires. The research was carried out cross-sectionally and data were taken from the staff of type A hospitals in Jakarta. The limitations of this study/implications of this study are that this study contributes to the theory by specifically analyzing the relationship between compensation and work/family conflict in a complex health service environment, one of the limitations of this study is the adoption of cross-sectional design; Future studies can be improved by using a variety of power gathering sources. The practical implication of this study is that this study highlights the magnitude of the influence of compensation and work/family conflict that is allegedly mediated by job satisfaction on employee retention. It can be concluded that compensation has a positive effect on job satisfaction, and work-family (W/F) conflict hurts job satisfaction, both of which have been proven to be true. In addition, W/F conflict has also been proven to have a negative influence on employee retention.